Meningkatkan Hasil Belajar Ipa Materi Gaya Dan Gerak Melalui Pendekatan Saintifik Dengan Menggunakan Model Problem Based Learning (Pbl) Di Kelas Iv Sdn 7 Pasir Putih - Hamriana Hamriana; Kasmawati Kasmawati; Ahmad Ahmad (Prodi PGSD Unsultra, 2021)
This study aims to improve science learning outcomes on the topic of force and motion through a scientific approach using the Problem Based Learning (PBL) model. This research is a classroom action research (CAR) conducted in two cycles, each consisting of two meetings. The study was carried out in April 2021 with 13 fourth-grade students of SD Negeri 7 Pasir Putih as the research subjects. The learning outcomes were obtained using multiple-choice tests. The results showed that the application of the Problem Based Learning (PBL) model could improve students’ learning outcomes. In the first cycle, 61.54% of students achieved a high category, while 38.46% were in the low category. In the second cycle, students’ performance improved, with 76.92% in the high category and only 23.07% in the low category. Thus, the application of the scientific approach through the Problem Based Learning (PBL) model proved effective in improving students’ learning outcomes in the topic of force and motion.